Problemática en la ejecución de sentencias de la Corte Interamericana de Derechos Humanos. El caso peruano - Castañeda Otsu, Susana Ynes (Revista de Derecho, 2019)
Peru has been the object of 28 judgments of conviction by the Inter-American Courtof Human Rights, what makes it the member country with the largest number of thesesentences. To date, it has complied with complete reparations in only two cases. Theauthor analyses the type of reparations ordered in the sentences, and the causes of thehigh level of non-compliance. Finally, she makes offers of modification to the specificregulation on the matter, unification of the jurisprudence on the part of the PenalRooms of the Supreme Court, between others, to solve partly detected problematic,although the Peruvian State has the obligation to comply with the Court judgmentson having had accepted his contentious jurisdiction.
Keywords: American Convention on Human Rights Inter-American Court of Human Rights; judgments and resolutions of supervision of judgment compliance; reparations; difficulties in judgment enforcement